Dasyleistes nom. nov. (Insecta: Heteroptera: Anthocoridae): a new replacement name for the junior homonym Dasypterus Reuter, 1872 - Swanson, Daniel R. (Zootaxa, 2019)
The purpose of this note is to replace the generic name Dasypterus Reuter, 1872, preoccupied by Dasypterus Peters, 1871, in accordance with the principles of the International Code of Zoological Nomenclature (ICZN 1999).